(untitled) (Raparin Journal of Humanities (RJH), 2026)
The aim of this study is to determine the level each of (self-efficacy and problem solving, and to determine difference in the level each of them according to variables (Gender and department satifaction) and also know the relationship between self-efficacy and problem-solving. The research population are koya university student’s for the academic year (2024-2025).the researcher randomly selected the faculty of humanities and social sciences as a sample and the researcher elected 500 students by random proportion sample, for measurement self-efficacy the researcher prepared The scale that consist of (19) items and is divided into four dimensions and the researcher did the psychometric for the scale such (types of validity and relialibility researcher used the scale (Cross, Bacon, Morris) for measure problem-solving which consists of (10) items and is divided into two dimensions the and the researcher did the psychometric for the scale such (types of validity and relialibility. The results of the study showed that the level of self-efficacy among students of Koya University is good and satisfied, so Problem solving among Koya University students is at a good level and they are satisfied with it. There is no statistically significant difference in each of self-efficacy and problem solving according to (gender and department satisfaction). There is also a strong direct relationship between self-efficacy and problem-solving. Finally, in the light of the findings, the researcher presented a number of recommendations and suggestions.